Correlation effects on resonant tunneling in one-dimensional quantum wires - Meden, Volker; Enss, Tilman (Physical review. B, Condensed matter and materials physics, 2005)
We study resonant tunneling in a Luttinger liquid with a double barrier enclosing a dot region. Within a microscopic model calculation the conductance G as a function of temperature T is determined over several decades. We identify parameter regimes in which the peak value Gp(T) shows distinctive power-law behavior. For intermediate dot parameters, Gp behaves in a nonuniversal way.